Evaluation of immunohistochemical expression of novel neuroendocrine marker INSM1 and histological tumor growth pattern in well-differentiated neuroendocrine tumors of the appendix: 15-year single tertiary center experience - Ali Koyuncuer; Tolga Canbak; Aylin Acar; Onur Şahin (Indian Journal of Pathology and Microbiology)
Introduction: Well-differentiated neuroendocrine tumors of the appendix (A-WDNET) are the most common neoplasms of the appendix but are rare and incidental. INSM1 is a novel transcription factor marker with high sensitivity and specificity for neuroendocrine differentiation. It may display architecturally diverse tumor growth patterns including solid, nest, insular trabecular, and acinar. Aims: The aim of this study was to determine the staining expression of INSM1 in A-WDNETs and detail the morphological tumor growth patterns. Materials and Methods: INSM1 immunohistochemistry was performed on 35 A-WDNET patients. Tumors were histologically classified according to their growth patterns. Results: Thirty-five patients, 60% of whom were male, had a mean age of 30 years at diagnosis and a mean tumor size of 0.9 cm. Eight percent of the tumors invaded the mucosa/submucosa, 34.3% showed invasion into the muscularis propria, 57.1% showed invasion into the subserosa or mesoappendix, LN metastasis was observed in two patients, lymph-vascular invasion in two patients, and perineural invasion in five patients. Ninety-four percent of the tumors were grade 1, the mitotic rate was >2% in two cases, and Ki-67 PI was >3% in two cases. INSM1 was positive in all cases (100%), 1+ 8.6%, 2+ 5.7%, 3+ 17.1%, 4+ 68.6%, weak staining in 11.4%, moderate staining in 22.9%, and strong staining in 67.7%. Type A histological growth pattern was observed in 54.3%, type B in 31.4%, and type C in 14.3% architecturally. Conclusions: INSM1 was positive in all A-WDNET morphological patterns and was 100% sensitive. INSM1 IHC can be used as an alternative to traditional neuroendocrine markers or in combination with the diagnosis of neuroendocrine tumors.